Análise dos genes CYP1A2, CYP3A4 e CYP3A5 na resposta à quimioterapia, no processo de tumorigênese e no microambiente metastático do osteossarcoma - Paolillo, Alini Trujillo [UNIFESP] (2016)
Introduction: Osteosarcoma (OS) derives from primitive mesenchymal cells and it is the most common malignant bone tumor in children and adolescents. OS treatment still using the same drugs since 1980s and survival rates have not improved since then, wherefore translational research is required to identify targets for novel treatment modalities Purpose: The present study investigated the expression of CYP (Cytochrome P-450) genes in OS, and if they play important role in treatment response and microenvironment to OS establishment, since the CYP enzymes mediate the metabolic activation of precarcinogens and participate in the inactivation and activation of anticancer drugs. The aim also was investigated if chemotherapy modulates CYP genes expression in OS cell lines. Methods: We investigated the expression of CYP1A2, CYP3A4 and CYP3A5 genes in 135 OS samples, including biopsy, bone tumor resection specimens, bone tumor adjacent (nonmalignant tissue), metastasis and lung adjacent to metastasis (nonmalignant tissue) samples. We used bone and lung normal tissues as control, obtained by healthy individuals and purchased. We also investigated in OS cell lines (Saos-2, MG-63, KHOS, U2-OS and M-OS) the modulation of CYP expression by chemotherapy drugs (cisplatin, doxorubicin and methotrexate) used in OS treatment. Results: The adjacent lung samples presented higher CYP1A2 gene expression than control of lung tissue (p=0.0256). The biopsy samples presented lower CYP3A4 gene expression than control of bone tissue (p=0.0314). The high CYP1A2 and CYP3A4 genes expression in bone tumor resection specimens were correlated with better event free-survival (p=0.0244) and good response (p=0.0484), respectively. Moreover, the high gene expression of CYP1A2, CYP3A4 and CYP3A5 were associated with toxicity events, such as infection, mucositis, fever, diarrhea, nephrotoxicity and hepatotoxicity. Furthermore, the chemotherapy drugs upregulated the CYP expression in OS cell lines. Conclusions: Our findings suggest that CYP genes play an important role in OS tumorigenesis, in primary and metastatic sites, as well in response to treatment.